Importance of Mentors in Polishing the Professional Development and Decreasing the Burnout among Medical Students: Role of Mentors in Professional Development and Decreasing the Burnout - Mudassar, Sahar; Ali, Mudassar; Habib, Bilal; Ahmad, Sundas; Ahmed, Shoaib; Imtiaz, Mavra (Pakistan Journal of Health Sciences, 2024)
Burnout among medical students is a significant concern, affecting not only their academic performance but also their overall well-being and professional development. Objective: To determine the relationship between mentor behaviors and burnout among students of medicine and development of professional behavior in medical schools. Methods: This Cross-sectional study was held among 3rd, 4th and final year medical students (N=300) and convenient sampling technique was used. The questionnaire was completed voluntarily by the students via online surveys evaluating the Professional Self-Identity Survey and the Mentor Behavior Scale. Multivariate regression analyzes were conducted to examine the associations between mentor behaviors with student burnout and their influence on the development of professional attitude. Results: In this analysis, 23.3% of students of medicine experienced burnout. Several factors were found to be strongly related with medical students’ burnout according to the multivariate analysis. Burnout was shown to be linked with participants who reported using medications (OR = 2.2, 95%CI: 1.2-3.95, p = 0.027). Burnout was also substantially correlated with medical students’ poor GPAs (GPA< 3.00) (OR = 3.1, 95%CI: 1.4-6.7, p = 0.001). Furthermore, burnout in medical students was substantially correlated with low to moderate levels of competency support from mentors (OR = 1.98, 95%CI: 1.01-3.2, p = 0.014). Conclusions: The influence of mentors’ behaviors on students of medicine is vital. Improving mentoring by denoting specific mentor behaviors can improve behavior of mentors.